Procrastination and projects - Philipp Külpmann (Bielefeld University, Center for Mathematical Economics (IMW), 2015)
In this paper I analyze a dynamic moral hazard problem in teams with imperfect monitoring in continuous time. In the model, players are working together to achieve a breakthrough in a project while facing a deadline. The effort needed to achieve such a breakthrough is unknown but players have a common prior about its distribution. Each player is only able to observe their own effort, not the effort of others. I characterize the optimal effort path for general distributions of breakthrough efforts and show that, in addition to free-riding, procrastination arises. Furthermore, in this model, procrastination is not a result of irrational behavior and is even present in the welfare-maximizing solution.
urn:nbn:de:0070-pub-27647303
Keywords: C72; C73; D81; D82; D83; H41; 330; Procrastination; Moral hazard in teams; Public good provision